The dynamics of phosphorus fractions and the factors driving phosphorus cycle in Zoige Plateau peatland soil. (September 2021) - Luo, Ling; Ye, Haoyang; Zhang, Danhua; Gu, Ji-Dong; Deng, Ouping
Abstract: Phosphorus (P) is an essential nutrient, limiting plant growth and microbial activity in many ecosystems. However, a few studies have been conducted to investigate P dynamics and the factors driving P dynamics in peatland soils. Therefore, this study chose Zoige Plateau peatland (the largest peatland in China) to reveal P dynamics and the possible driving factors through fractionating soil P and investigating a series of abiotic and biotic factors. It is found that season, peatland type, and soil depth could strongly affect P dynamics. H2 O–P and NaHCO3 –P (labile P) had lower content, while NaOH–P, HCl–P, Mix-P, and Residual-P (non-labile P) were the dominant fractions. Besides, the sum of P fractions was higher than the traditional measurement of total P, suggesting P storage might be underestimated in peatland soils. Moreover, it is observed that biotic factors affected P fractions more than abiotic factors, and fungi affected refractory P more than bacteria. This study provides essential information for understanding P cycling in peatland soils and emphasizes specific microbes related to P cycling, which should be paid more attention to in the future. Highlights: Season, peatland type, and soil depths strongly affected P fractions in Zoige soil. NaOH–P, HCl–P, Mix-P, and Residual-P were the dominant P fractions. The sum of P fractions suggested P storage might be underestimated. Biotic factors affected P dynamics more than abiotic factors in peatland soils. Fungi played crucial roles in accumulating and solubilizing refractory P.